Urban daily lives and out-of-home food consumption among the urban poor in Nigeria: A practice-based approach - Adeosun, Kehinde Paul; Greene, Mary; Oosterveer, Peter (Elsevier, 2022)
Understanding the interaction between urban daily lives and patterns of food consumption in the Global South is important for informing health and sustainability transitions. In recent years, the lives of poor urban dwellers have undergone significant transformations which have been associated with shifts in patterns of daily food consumption from household-based towards primarily out-of-home. However, as of yet, little research has explored how changing everyday contexts of consumers' lives interrelate with their food vending-consumption practices. This study seeks to understand the interrelations between everyday urban lives and out-of-home food consumption practices among the urban poor in Ibadan, Nigeria. A situated social practice approach is employed to understand how everyday contexts shape practices of out-of-home food vending consumption. Multiple methods were employed, including GIS mapping of food vending outlets, quantitative consumer surveys, in-depth consumer interviews, and participant observation. The study provides an overview of food vending-consumption practices in terms of the socio-demographic situation of consumers and the embeddedness of food vending in the practice arrangements making up their daily lives. The findings reveal three key daily life practices that interlock with their ready-to-eat foods consumption practices: daily mobility practices, working arrangements, and domestic engagements These three categories of daily urban practices that have undergone rapid transformation in line with socio-economic change and urbanisation and emerged as particularly important in shaping out-of-home food consumption. The paper concludes by considering the importance of understanding the embeddedness of food vending practices in the daily lives of the urban poor for sustainable food systems transitions in the Global South.